2015
DOI: 10.1007/s10926-014-9559-9
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of the Spinal Function Sort in Patients with Sub-acute Whiplash-Associated Disorders

Abstract: Purpose To extensively analyze the measurement properties the Spinal Function Sort (SFS) in patients with sub-acute whiplash-associated disorders (WAD). Methods Three-hundred-two patients with WAD were recruited from an outpatient work rehabilitation center. Internal consistency was assessed by Cronbach’s α. Construct validity was tested based on eight a priori hypotheses. Structural validity was measured with principal component analysis (PCA). Test–retest reliability and agreement was evaluated in a sub samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
2
14
0
1
Order By: Relevance
“…The most relevant findings from the quantitative analysis of 565 SFS’s obtained in previous studies [ 17 , 21 , 28 ] were the high Cronbach’s alpha values of 0.98 of all items, and 0.96 if the sample was split into two groups—one group with even and one group with odd numbered items; six items loaded on any of the with PCA identified six components of the SFS; mean square fit values from the Rasch analysis between 0.5 and 1.5 for all items except for items 45–48 with values >2.0; and large floor effects of four items depicting lifting tasks of 50 kg (items 45–48). These findings strongly support item reduction and modification of the SFS, as suggested in previous studies [ 17 , 18 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…The most relevant findings from the quantitative analysis of 565 SFS’s obtained in previous studies [ 17 , 21 , 28 ] were the high Cronbach’s alpha values of 0.98 of all items, and 0.96 if the sample was split into two groups—one group with even and one group with odd numbered items; six items loaded on any of the with PCA identified six components of the SFS; mean square fit values from the Rasch analysis between 0.5 and 1.5 for all items except for items 45–48 with values >2.0; and large floor effects of four items depicting lifting tasks of 50 kg (items 45–48). These findings strongly support item reduction and modification of the SFS, as suggested in previous studies [ 17 , 18 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, the rating of 50 items is time-consuming, and a shorter version of the SFS is warranted. It has also been suggested that the number of SFS items could be reduced by half because of redundant items [ 12 , 13 ]. Another critique was that the SFS does not include pictures of prolonged work postures, ambulation and the images are outdated [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relevant part was selected after expert evaluation and testing within the clinical setting. SFS has very good retest-reliability (ICC = 0.98; 95% CI: 0.97-1.00) (Borloz, Trippolini, Ballabeni, Luthi, & Deriaz, 2012;Trippolini, Dijkstra, Geertzen, & Reneman, 2015).…”
Section: Primary Outcome Variablesmentioning
confidence: 99%